ChemInform Abstract: The Development of Synthetic Antitumor Vaccines from Mucin Glycopeptide Antigens. Issue 32 (18th July 2013) - Gaidzik, Nikola; Westerlind, Ulrika; Kunz, Horst
Abstract Review: 77 refs.